Friction and wear of sand-contaminated lubricated sliding - Mohamed Ahmed Ramadan (Friction)
Abstract This paper reports a test investigation of friction and wear responses from sand contaminated lubricated sliding. The influence of sand contaminants on wear and friction is characterized. Analyses are completed utilizing segments of piston ring sliding against the cylinder liner. Paraffin oil, with and without sand contaminants, is utilized. The effects of the concentration and particle size of sand are examined. Based on the observations in the present work, we found that friction and wear increase with sand concentration in the lube. Solid proposals ought to be considered, in order to enlighten the general population on the importance of changing a car engine’s oil filter regularly.